2021
DOI: 10.1111/mcn.13251
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing breastfeeding practices in China: A meta‐aggregation of qualitative studies

Abstract: The World Health Organization recommends that women exclusively breastfeed until their babies are 6 months old and continue to breastfeed while introducing complementary foods. A meta-aggregation methodology was used to systematically review and synthesise the qualitative studies on factors influencing breastfeeding practices of healthy Chinese women in Greater China. English and Chinese databases were searched to identify peer-reviewed qualitative studies (published 2008-2019).Relevant data were extracted, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 54 publications
(59 reference statements)
1
12
1
Order By: Relevance
“…Breastfeeding practices are in uenced by various factors including maternal age, education level, family income and so on. A review study of meta-aggregation of qualitative studies showed that maternal perceptions and self-e cacy, family support, social expectations and policy as factors in uencing breastfeeding in China (19). The present study found no signi cant associations between maternal age, mothers' occupation, and parity and planning for exclusive breastfeeding within 6 months postpartum.…”
Section: Discussioncontrasting
confidence: 76%
“…Breastfeeding practices are in uenced by various factors including maternal age, education level, family income and so on. A review study of meta-aggregation of qualitative studies showed that maternal perceptions and self-e cacy, family support, social expectations and policy as factors in uencing breastfeeding in China (19). The present study found no signi cant associations between maternal age, mothers' occupation, and parity and planning for exclusive breastfeeding within 6 months postpartum.…”
Section: Discussioncontrasting
confidence: 76%
“…In addition, for women, it reduces the risk of type 2 diabetes as well as ovarian and breast cancer (Victora et al, 2016). China has a very low rate of EBF-around 29% in 2019(China Development Research Foundation, 2019) and a median breastfeeding duration is 8.6 months (Wu et al, 2021). By contrast, other middle-income countries like India and Brazil have much higher EBF rates, with 55% (estimated in 2015) and 41% (estimated in 2008), respectively (The World Bank, 2019), and longer breastfeeding duration (Neves et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that being cared for by a yuesao during this stage can help improve the health of mothers and babies, 38 39 reduce postpartum depression 40 41 and facilitate breast feeding. 42 Therefore, hiring a yuesao to prepare postpartum foods and help with household and childcare tasks has become increasingly popular in many urban families. However, not everyone can afford their services.…”
Section: Discussionmentioning
confidence: 99%
“…Chinese tradition dictates that new mothers stay home and rest for a ‘confinement period’ of about 1 month (28−42 days) after giving birth, which is thought to facilitate recovery. Previous studies reported that being cared for by a yuesao during this stage can help improve the health of mothers and babies,38 39 reduce postpartum depression40 41 and facilitate breast feeding 42. Therefore, hiring a yuesao to prepare postpartum foods and help with household and childcare tasks has become increasingly popular in many urban families.…”
Section: Discussionmentioning
confidence: 99%